THE ESSENCE OF INSURANCE AND THE MECHANISM OF IMPLEMENTATION OF PROPERTY INSURANCE AT THE PRESENT STAGE - Sh. F. Kobilzhonova (European Science Publishing, 2023)
The article is devoted to the essence of insurance and the mechanism of realization of property insurance at the present stage of economic development. Insurance is an important element of the functioning of the financial system of the state, capable of ensuring the continuity of social reproduction, depending on the negative consequences of natural disasters, accidents, natural and industrial disasters and other unforeseen events that cause high risks of property loss, as well as guarantee social protection of the population and stabilize the process of investing in the economy. In the process of forming a market infrastructure, aspects of economic activity insurance acquire special importance. Insurance affects the development and improvement of investment opportunities, as well as the increase in the welfare of the nation. Successful development of the insurance market is impossible without precise regulation and deliberate legislative acts defining the organization and activities of insurers. The insurance market in our country is developing quite dynamically and is able to outpace the growth rates in most of the leading countries. With the use of civilized forms, Russian insurance uses insurance products that are not only not inferior to foreign analogues, but also often look preferable by many criteria. There are many types of insurance in Uzbekistan at the present stage. To date, property insurance in Uzbekistan is an insurance industry in which the object of insurance relations are property interests and property in various forms (for example, buildings, structures, equipment, and so on). The property insurance market in our country is developing quite rapidly and if there are no major turning points in society in the future, then after a while insurance can become one of the main factors protecting the interests of citizens and legal entities that own any property.
Keywords: acquisition, insurance contract, income, property, property interest, liability, insurance, policyholder, insurer, insurance activity, insurance interest, insurance premium, insurance franchise, insurance market, insurance products, subrogation.